2006
DOI: 10.1002/srin.200606383
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of Manganese Sulphide Formation during Solidification, Part II: Correlation of Solidification and MnS Formation

Abstract: The high temperature properties of steels depend on the solidification parameters and the formation parameters of manganese sulphide precipitates. Therefore, the occurrence of MnS precipitations in relation to primary and secondary microstructures was studied for different steel grades with a primary delta-ferritic solidification or a primary austenitic solidification. The liquidus and solidus temperatures as well as the by-transformation temperature were calculated thermodynamically and measured by a DTA anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…Diederichs et al . 11,12 modified the model developed by Schwerdtfeger 9,10 by considering the concentrations of manganese and sulphur, as well as the dendrite arm spacing in medium-carbon steel.…”
Section: Introductionmentioning
confidence: 99%
“…Diederichs et al . 11,12 modified the model developed by Schwerdtfeger 9,10 by considering the concentrations of manganese and sulphur, as well as the dendrite arm spacing in medium-carbon steel.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9] Depending on the material and post processing techniques employed the MnS inclusions transform into globular or plate like shapes. [10,11] The positive effect of adding Sulfur to steel alloys for improving the machinability, reduction in tool wear rate and improved chips flow was discovered quite early. [12] It was shown that for a constant speed and feed rate the tool life can be increased up to a factor of 10 by adding 0.4% Sulfur.…”
Section: Introductionmentioning
confidence: 99%
“…During hot rolling, these manganese sulphide inclusions, which are plastic at elevated temperature, become highly elongated in the rolling direction and drastically reduce ductility and specifically impact strength in the transverse direction of rolled products. The deleterious effect of such inclusions on formability can be minimized or even eliminated by sulphide shape control (Paul & Ray, 1997) but, by contrast, these manganese sulphides can be effectively utilized to control micro‐structural development (Wakoh et al , 1996; Oikawa et al , 1997; Tsunekage & Tsubakino, 2001; Diederichs et al , 2006).…”
Section: Introductionmentioning
confidence: 99%